Distractions and interruptions in a surgical room: perception of nursing staff - Helen Cristiny Teodoro Couto Ribeiro; Thatiane Marcélia Rodrigues; Sara Araújo Ferreira Teles; Rafaela Carvalho Pereira; Liliane de Lourdes Teixeira Silva; Luciana Regina Ferreira da Mata (Universidade Federal do Rio de Janeiro, 2018)
Abstract Objective: To understand the perception of nursing staff about intraoperative distractions and interruptions. Methods: An exploratory qualitative study was performed with 16 nursing professionals of a surgical center in Minas Gerais. The data were collected through a semi-structured interview and thematic content analysis was performed. Results: When reflecting on the occurrence of distractions and interruptions of intraoperative activities, nursing professionals define, identify and value events in a heterogeneous way, but believe that distractions and interruptions negatively affect both the quality of the work environment and the safety of care provided to the surgical patient. Factors contributing to the occurrence of distractions and interruptions are related to aspects inside the operating room such as equipment failure and use of cell phones and to external factors such as verbal messages given at the operating room door. Incidents have been reported due to distractions, but there are no established actions to minimize these events. Conclusion: This study indicates the importance of implementing strategies that minimize the occurrence of distractions and interruptions of intraoperative activities in order to plan surgical care better, and prevent and mitigate harm to patients.